Pengaruh Model Pembelajaran Problem Based Learning (PBL) terhadap Kemampuan Berpikir Kritis IPA Siswa Kelas V SDN Cogreg I Kabupaten Tangerang - Puspa Anggraini; Aam Amaliyah; Candra Puspita Rini (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
This research is backgrounded by low student learning outcomes which refers to students' critical thinking ability hampered by the use of learning models. This study aims to determine the difference in science critical thinking skills between students who are given the Problem Based Learning (PBL) learning model and students who are given conventional learning models. This research uses a Quasi-Experimental research method with a Nonequivalent Control Group Design design. The population subjects in this study were grade V students of SDN Cogreg 1 Tangerang Regency by taking a sample of two classes of 64 students, V A class which totaled 32 people as a control class, and V B class which amounted to 32 people as an experimental class. Data collection technique using critical thinking ability test question instruments in the form of 10 questions. Based on the results of hypothesis test data analysis using a t-test at a significance level of 0.05, it is calculated > ttabel which is 2.11 > 2.00, so that H0 is rejected and accepted. Thus, it can be said that there are differences in the ability to think critically in science between students who are given the Problem Based Learning (PBL) learning model and students who are given conventional learning models.